Direct microstrip line-fed dielectric resonator antenna array. Issue 12 (12th August 2016) - Rana, Biswarup; Parui, Susanta Kumar
Abstract: In this paper, a 1×4 rectangular dielectric resonator antenna array is designed using direct microstrip lines at the center frequency of 6.7 GHz for obtaining higher directive gain. A prototype has been fabricated with Arlon AD270 substrate and experimental measurements have been carried out. The array offers an impedance bandwidth of 9.6% and a maximum gain of 11.8 dBi at the operating frequency. A close agreement between simulated and measured results has been obtained.